A cross-sectional analysis of four common clinical decision rules for pulmonary embolism, Mashhad, Iran - Solmaz Hassani; Neshat Najaf Najafi; Amirhossein Khodadadi; Fahimeh Gandomi; Mahnaz Amini (Journal of Cardiovascular and Thoracic Research)
Introduction: Pulmonary embolism (PE) is a potentially fatal condition. Several non-invasive clinical decision rules (CDRs) were developed for the safe exclusion of PE. All CDRs used to safely rule out PE have been created and tested within hospital or acute care environments. However, CDRs that are designed in one specific setting may not perform as effectively when used in a different setting. In this study, we aimed to compare the performance of four common CDRs; Wells Score, Simplified Wells Score, revised Geneva Score, and simplified revised Geneva Score. Methods: This was a cross-sectional study in which patients suspected of PE presenting to Imam Reza Hospital or Ghaem Hospital were recruited from September 23, 2013, to March 19, 2016 in Mashhad, Iran. The specificity, sensitivity, and accuracy were utilized as metrics to compare the CDRs in our region. Results: Two hundred and forty patients were included in the study. The mean age of patients was 57.91±19.97 years, and 54.16% of them (n=130) were female. 120 patients were confirmed to have PE with CT angiography. Wells score showed the highest sensitivity (90.4%) and revised Geneva score represented the highest specificity (84.9%). The highest accuracy belongs to the simplified Wells score (62.3%). Conclusion: In this study, we demonstrated that the Wells criteria with its high sensitivity, can be used as a score for screening, and the revised Geneva score with its high specificity, can be used in the second stage for healthy people who have been diagnosed as unhealthy by the Wells score.